Transorbital sonographic evaluation of normal optic nerve sheath diameter in healthy volunteers in Bangladesh - Maude, R; Hossain, M; Hassan, M; Osbourne, S; Sayeed, K; Karim, MR; Samad, R; Borooah, S; Dhillon, B; Day, N; Dondorp, A; Maude, R (Public Library of Science, 2013)
INTRODUCTION: Measurement of optic nerve sheath diameter (ONSD) by ultrasound is increasingly used as a marker to detect raised intracranial pressure (ICP). ONSD varies with age and there is no clear consensus between studies for an upper limit of normal. Knowledge of normal ONSD in a healthy population is essential to interpret this measurement. METHODS: In a prospective observational study, ONSD was measured using a 15 MHz ultrasound probe in healthy volunteers in Chittagong, Bangladesh. The aims were to determine the normal range of ONSD in healthy Bangladeshi adults and children, compare measurements in males and females, horizontal and vertical beam orientations and left and right eyes in the same individual and to determine whether ONSD varies with head circumference independent of age. RESULTS: 136 subjects were enrolled, 12.5% of whom were age 16 or under. Median ONSD was 4.41 mm with 95% of subjects in the range 4.25-4.75 mm. ONSD was bimodally distributed. There was no relationship between ONSD and age (≥4 years), gender, head circumference, and no difference in left vs right eye or horizontal vs vertical beam. CONCLUSIONS: Ultrasonographic ONSD in Bangladeshi healthy volunteers has a narrow bimodal distribution independent of age (≥4 years), gender and head circumference. ONSD >4.75 mm in this population should be considered abnormal.